2011
DOI: 10.1007/s13197-011-0546-2
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of process parameters for microwave assisted convective dehydration of ginger

Abstract: Ginger (Zingiber Officinale, Cv. Suprava) slices (4 mm thick) were dehydrated at 25°, 40°, 50°and 60°C with three different microwave power levels, viz. 120, 240, and 360 W in microwave assisted convective dryer up to 0.07 g moisture/g dry solid to observe the feasibility of microwave assisted convective drying for ginger. The samples were also dried without application of microwaves (0 W) at the above air temperatures. The final product quality was compared in terms of rehydration characteristics, oleoresin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…After 30 min of rehydration, RR of chunks dried at 700 W started declining and remained lower to that of the chunks dried at 650 W. Similar to our finding, Mohanta et al. (2014) also observed less rehydration ability in ginger slices when the microwave power increased from 120 W because of shrinkage of cell structure caused by faster drying rate.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…After 30 min of rehydration, RR of chunks dried at 700 W started declining and remained lower to that of the chunks dried at 650 W. Similar to our finding, Mohanta et al. (2014) also observed less rehydration ability in ginger slices when the microwave power increased from 120 W because of shrinkage of cell structure caused by faster drying rate.…”
Section: Resultssupporting
confidence: 90%
“…RR of chunks dried at 600 W was the lowest among all samples owing to its higher moisture content and a tight microstructure which limits further diffusion of moisture into the muscle. After 30 min of rehydration, RR of chunks dried at 700 W started declining and remained lower to that of the chunks dried at 650 W. Similar to our finding, Mohanta et al (2014) also observed less rehydration ability in ginger slices when the microwave power increased from 120 W because of shrinkage of cell structure caused by faster drying rate.…”
Section: Rehydration Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…MWC being the fastest drying method employed for pineapple slices in this study, resulted in irreversible cellular shrinkage, which may responsible for hindrance in water uptake during rehydration operation. Mohanta et al [26] observed similar rehydration characteristics for microwave convective dried ginger. An increase in RR was noted with increasing rehydration temperature from 20 to 80 °C, this may be supported by the fact that with a rise in temperature, moisture also penetrated to the dried product at a higher rate.…”
Section: Resultsmentioning
confidence: 72%
“…These results confirm a denaturation of ginger characteristics when using this drying method at a high-power level. Testing a microwave assisted convective dryer at power level up to 240 W, Mohanta et al [33] rather obtained accepted infusions. This power level is therefore a key parameter to take into consideration when performing such treatment.…”
Section: Discussionmentioning
confidence: 99%